Hubungan antara Fanatisme dengan Perilaku Konsumtif pada Remaja Penggemar K-Pop - Ulfah, Sarini; Haryad, Rudi (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
The purpose of this study was to determine the relationship between fanaticism and the level of consumptive behavior among young K-Pop fans at SMKN 1 Martapura (Class X and IX) Department of Marketing. quantitative with the type of correlational research thataims to see the relationship between fanaticism (X) with consumptive behavior (Y) on K-Pop fans. The data collection technique in this study used a questionnaire using a Likert Scale, the sample calculation using the Non-Random Sampling Technique. The population in this study was 120 people with a sample of 108 people. The instrument in this study uses a fanaticism scale and a consumptive behavior scale that was adopted from Kartika Adriani's Thesis in 2021. Based on the results of the Product Moment correlation test with the value of Sig. 0.000 > 0.05 which means that there is a relationship between fanaticism and consumptive behavior in young K-Pop fans at SMK Negeri 1 Martapura class 10 & 11 majoring in Marketing.